Knee Flexor: Extensor isokinetic ratios in young male gymnasts and swimmers - Siatras, T.; Mameletzi, D.; Kellis, S. (Pediatric Exercise Science, 2004)
The purpose of the study was to determine young male gymnasts' and swimmers' knee flexor:extensor (F:E) ratios during isokinetic testing at different velocities. Nine gymnasts (10.3 ± 0.5 years) and 14 swimmers (10.5 ± 0.5 years) participated. Concentric isokinetic peak torque was measured by a CybexÒ Norm dynamometer at different angular velocities (60,120, and 180°/s) during unilateral knee extensions and flexions after gravity correction. Significant differences were found only in gymnasts' knee F:E peak-torque ratios between the angular velocities of 60 and 120°/s (p < .01), as well as 60 and 180°/s (p < .01), whereas swimmers' ratios were unchanged. Gymnasts presented significantly higher F:E ratios than swimmers did at the angular velocities of 120°/s (p < .01) and 180°/s (p < .001). The reciprocal ratios provided some indication that the training context of young athletes can influence the balance between agonistic and antagonistic activity of the lower limbs' major muscle groups.